STUDI KASUS ANALISIS ASUHAN KEPERAWATAN PASIEN DIABETES MELITUS DENGAN MASALAH KEPERAWATAN GANGGUAN POLA TIDUR YANG DIBERIKAN KOMBINASI SLEEP HYGIENE DAN AROMATERAPI LAVENDER - Somowati, Ni Ketut; Prihandhani, IGAA Sherlyna; Yunita Sari, NLP Dian (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Complaints of patients with Type 2 DM such as nocturia, frequent thirst, frequent hunger, skin itching, tingling, leg cramps, pain and physical discomfort that can cause sleep disturbances and result in poor sleep quality. Maintaining and maintaining sleep quality is one of them through the provision of sleep hygiene and lavender aromatherapy. The purpose of writing this scientific paper is to determine the analysis of nursing care for patients with diabetes mellitus with nursing problems of sleep pattern disorders given a combination of sleep hygiene therapy and lavender aromatherapy. The method in writing this scientific paper is a case study involving three DM patients. Data collection techniques used interviews, observations, physical examinations, and documentation studies. The nursing problem found was disturbed sleep patterns associated with poor sleep control and clinical manifestations of DM disease. The main intervention is sleep support by providing a combination of sleep hygiene and lavender aromatherapy which is done once a day for 60 minutes and repeated for three days. The provision of sleep hygiene and lavender aromatherapy is effective in reducing complaints of sleep pattern disorders experienced by the three DM patients. Providing education related to sleep hygiene and also making SOPs related to complementary therapies that can be applied in DM patients.